Ab initio perceptual learning of foreign language sounds: Spanish consonant acquisition by Chinese learners. (June 2017) - Gong, Jian; García Lecumberri, María Luisa; Cooke, Martin
Abstract: High-variability phonetic training is effective in the acquisition of foreign language sounds. Previous studies have largely focused on small sets of contrasts, and have not controlled for the quantity of prior or simultaneous exposure to new sounds. The current study examined the effectiveness of phonetic training in full-inventory foreign language consonant acquisition by listeners with no previous exposure to the language. Chinese adult listeners underwent an intensive training programme, bracketed by tests that measured both assimilation of foreign sounds to native categories, and foreign category identification rates and confusions. Very rapid learning was evident in the results, with initial misidentification rates halving by the time of the mid-test, and continuing to fall in subsequent training sessions. Changes as a result of training in perceptual assimilation together with improved identifications and reduced response dispersion suggest an expansion of listeners' native categories to accommodate the foreign sounds and an incipient process of foreign language category formation.